The Role of Technology in Facilitating EFL Learning: A Case Study Approach - Sari, Nurhidayah (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2024)
This research investigates how digital tools and resources are integrated into English as a Foreign Language (EFL) education to enhance learning outcomes. The study employs qualitative through interviews, questionnaires, and classroom observations. Interviews with 6 lecturers and 74 students as the samples provide in-depth insights into their experiences and perceptions. Classroom observations offer real-time evidence of how technology is used in practice, highlighting both its benefits and obstacles. Data is analyzed using thematic analysis for qualitative, allowing for a comprehensive understanding of the role of technology in EFL learning at the English Language Learning and Education Study Program of University of Pahlawan Tuanku Tambusai during February to June 2024. The results show that the use of technology has been positively perceived by both students and lecturers, who recognize the ability to make learning more accessible, interactive, and tailored to individual needs. The widespread use of tools such as language learning apps, online resources, and multimedia presentations has contributed to more effective and enjoyable learning experiences. Despite these benefits, the research also identified significant challenges, including technical issues, inconsistent access to devices, and varying levels of digital literacy among students. These challenges sometimes hinder the seamless integration of technology into EFL learning. The technology has greatly contributed to the success of EFL learning at Universitas Pahlawan Tuanku Tambusai, addressing the challenges identified will be crucial for maximizing its potential. By investing in better support systems, infrastructure, and training, the university can further enhance the effectiveness of technology in fostering English language proficiency among its students.